In vitro and in vivo comparison of MRI chemical exchange saturation transfer (CEST) properties between native glucose and 3‐O‐Methyl‐D‐glucose in a murine tumor model. (22nd August 2021) - Anemone, Annasofia; Capozza, Martina; Arena, Francesca; Zullino, Sara; Bardini, Paola; Terreno, Enzo; Longo, Dario Livio; Aime, Silvio
Abstract : D‐Glucose and 3‐O‐Methyl‐D‐glucose (3OMG) have been shown to provide contrast in magnetic resonance imaging‐chemical exchange saturation transfer (MRI‐CEST) images. However, a systematic comparison between these two molecules has yet to be performed. The current study deals with the assessment of the effect of pH, saturation power level (B1 ) and magnetic field strength (B0 ) on the MRI‐CEST contrast with the aim of comparing the in vivo CEST contrast detectability of these two agents in the glucoCEST procedure. Phosphate‐buffered solutions of D‐Glucose or 3OMG (20 mM) were prepared at different pH values and Z‐spectra were acquired at several B1 levels at 37°C. In vivo glucoCEST images were obtained at 3 and 7 T over a period of 30 min after injection of D‐Glucose or 3OMG (at doses of 1.5 or 3 g/kg) in a murine melanoma tumor model (n = 3–5 mice for each molecule, dose and B0 field). A markedly different pH dependence of CEST response was observed in vitro for D‐Glucose and 3OMG. The glucoCEST contrast enhancement in the tumor region following intravenous administration (at the 3 g/kg dose) was comparable for both molecules: 1%–2% at 3 T and 2%–3% at 7 T. The percentage change in saturation transfer that resulted was almost constant for 3OMG over the 30‐min period, whereas a significant increase was detected for D‐Glucose. Our results show similar CEST contrast efficiency but different temporal kinetics for the metabolizable and the nonmetabolizable glucose derivatives in a tumor murine model when administered at the same doses. Abstract : This study investigated the CEST properties of D‐Glucose and 3‐O‐Methyl‐D‐glucose (30MG) in vitro and after intravenous injection in a murine melanoma model. A marked and opposite pH dependence of the CEST contrast was observed in vitro for D‐Glucose and 3OMG, whereas both molecules showed a similar CEST enhancement following the in vivo administration at 7 T, but a reduced detectability at 3 T.